2021
DOI: 10.1097/mao.0000000000003306
|View full text |Cite
|
Sign up to set email alerts
|

Forces Required for Isolated Malleus Shaft Fractures

Abstract: Background and Hypothesis: Isolated malleus shaft fractures are rare cases. A commonly reported cause is a finger pulled out from a wet outer ear canal after a shower or bath. The objective was to investigate experimentally the mechanism and forces needed to establish an isolated malleus shaft fracture. Methods: Ten fresh-frozen human temporal bones were adapted to allow visual inspection of the structures involved while negative pressure trauma was applied. Thirty malleus bones were broken and the required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The tensor tympani tendon has been suggested to protect against outward displacement of the ossicular chain (Hüttenbrink, 1989). However, we have previously reported that the ligament by itself has very little effect in limiting the outward movement of the tympanic membrane and malleus (Rönnblom et al, 2021). In the same study, we found the combination of a negative pressure created by a finger being extracted from a wet ear canal and a simultaneous counteracting reflexive force by the tensor tympani muscle could cause an isolated malleus fracture with an intact tympanic membrane.…”
Section: Discussionmentioning
confidence: 97%
“…The tensor tympani tendon has been suggested to protect against outward displacement of the ossicular chain (Hüttenbrink, 1989). However, we have previously reported that the ligament by itself has very little effect in limiting the outward movement of the tympanic membrane and malleus (Rönnblom et al, 2021). In the same study, we found the combination of a negative pressure created by a finger being extracted from a wet ear canal and a simultaneous counteracting reflexive force by the tensor tympani muscle could cause an isolated malleus fracture with an intact tympanic membrane.…”
Section: Discussionmentioning
confidence: 97%
“…Upon sudden withdrawal of the finger from the EAC, sudden hearing loss and otalgia occur. The fracture is a result of opposing forces applied at different areas of the malleus—negative pressure applied to the manubrium laterally by abrupt finger removal and concomitant medial pull to the malleus head created by the tensor tympani 30 . The TM generally does not perforate at the same time given that it is more malleable and tolerant of abrupt pressure changes.…”
Section: Discussionmentioning
confidence: 99%